The practicality of student worksheets on the Scientific Creativity project-based Learning (SCPjBL) model to improve scientific creativity as a creative process for Physics Education students - Sumo, Maimon; Jatmiko, Budi; Supardi, Zainul Arifin Imam (PT. Riset Press International, 2024)
The aim of this reseach was to describe the practicality of the SCPjBL model, based on the results of the implementation of scientific investigations to improve students' scientific creativity on Student Worksheets (LKM). The method in this study is the development of a modified model and applied in universities in 2024. The sample in this study was 90 students from two different universities. Data were collected based on the results of validation and observation of the implementation of the SCPjBL model. The assessment instrument used an implementation observation sheet carried out by two observers. The observation sheet was filled in by four observers who were divided into two observers who were tasked with observing the implementation of the SCPjBL model phase, and two others observed student activities, the results of the observations were then analyzed quantitatively. The results of the study were in the form of implementation results by obtaining an average score of 3.72 with an average validity percentage of 91% with a very practical category. The results of the practicality of the SCPjBL model and its supporting devices obtained a score of 3.56 with an average implementation percentage reaching 91%. Based on the results of the study, the SCPjBL model was declared practical and feasible for use.